2020
DOI: 10.1186/s12884-020-03385-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn healthcare practices: assessment of the uptake of lifesaving services in Hoima District, Uganda

Abstract: Background The current maternal mortality ratio in Uganda is 336 maternal deaths per 100,000 live births. Infant mortality is 43 deaths per 1000 live births, with 42% of the mortality occurring during the neonatal period. This might be related to a weak health system in the country. This study aimed at assessing the uptake of lifesaving services during pregnancy and childbirth in Hoima District, Uganda. Methods The study used a cross-sectional quantitative design among 691 women with a child under 5 years. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Uganda’s perinatal mortality has stagnated at 40 per 1,000 pregnancies over the last decade [ 8 , 9 ]. Over the same period, the utilization of maternal healthcare services has generally improved, but maternal mortality rate has remained unacceptably high at 336 maternal deaths per 100,000 live births [ 9 , 10 ]. It is estimated that 80% of maternal deaths and 66% of neonatal deaths in the world could be averted by ensuring that women have access to quality and effective maternal healthcare services especially during childbirth and in the first week of life [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uganda’s perinatal mortality has stagnated at 40 per 1,000 pregnancies over the last decade [ 8 , 9 ]. Over the same period, the utilization of maternal healthcare services has generally improved, but maternal mortality rate has remained unacceptably high at 336 maternal deaths per 100,000 live births [ 9 , 10 ]. It is estimated that 80% of maternal deaths and 66% of neonatal deaths in the world could be averted by ensuring that women have access to quality and effective maternal healthcare services especially during childbirth and in the first week of life [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a positive relationship between maternal education and utilization of MHC [ 7 – 9 ]. However, for the case of Uganda, most existing studies are unable to explain whether the link between education and maternal health is attributable to other correlated factors such as economic growth and household income among others.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…Ensuring that mothers and newborns receive timely, high-quality care during these critical periods is essential. At baseline, attending four or more ANC was 55.1% [ 4 ]; therefore, this means almost half of the mothers miss goal oriented services such as screening for, preventing, and treating HIV, anemia, malaria, urinary tract infections, pre-eclampsia/eclampsia, preterm delivery, and other complications that can be life-threatening to both mother and baby [ 5 ]. Supporting women to deliver under the supervision of a skilled birth attendant and having the necessary supplies is key to preventing leading causes of maternal and newborn deaths [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The home visits are implemented for pregnant mothers, and after birth, the children are followed up and registered. VHTs also monitor the use of certain services, for instance whether mothers come for antenatal care at the health facility and whether they have had an HIV test [ 4 ].…”
Section: Introductionmentioning
confidence: 99%